PENGARUH PENERAPAN IMOD TERHADAP KETERAMPILAN DEKLAMASI PUISI SISWA KELAS IV SDN RAMPAL CELAKET 2 MALANG - Desiana Rose Wahyuningdiyah (ELEMENTARY SCHOOL JOURNAL PGSD FIP UNIMED, 2020)
Literary learning is very important for children's education because it includes personal values and educational values. Based on observations in class IV SDN Rampal Celaket 2 Malang, learning Indonesian especially in poetry declamation material is still not optimal. Therefore it is necessary to have an action that can affect the poetry declamation skills of students. The purpose of this study was to determine the effect of Imod on poetry declamation skills in fourth grade students of SDN Rampal Celaket 2 Malang. This study uses a quantitative research approach and type, with quasi-experimental research designs. The form used is Nonequivalent Control Group Design. Based on testing the hypothesis with the Mann Whitney U test, the significance level of 0.000 ˂ 0.05 results, the null hypothesis (H0) is rejected and the initial hypothesis (Ha) is accepted. This means that the application of Imod significantly influences the poetry reclamation skills of fourth grade students of SDN Rampalcelaket 2 Malang. Keywords : Declamation Skill, Imod, Poetry